The Development of Digital Books Aided Augmented Reality (AR) to Improve Self Efficacy in Favor of Distance Learning - Siregar, Tiur Malasari; Ritonga, Arnah; Darma, Jufri; Dongoran, Faisal Rahman (Journal of Education, Health and Sport, 2022)
This study aims to create a Digital Book mathematical economics to improve the self-efficacy of students, where Media Powtoon, Augmented Reality (AR) and application Kahoot already present in the design of digital books. To see the feasibility of the book, the attractiveness of the book and the effectiveness of using AR-assisted Economic Mathematics Books to increase student self-efficacy. The research method used in this research is the development of the ADDIE model which has five stages of research implementation, namely Analysis, Design, Develop, Implement, and Evaluate. Through these five stages, researchers will develop an AR-assisted Mathematics Economics book. In this book, several applications will collaborate in providing the presentation of the material in the form of learning videos using the application Powtoon, displaying animations with Augmented Reality (AR) and evaluating learning outcomes using the application Kahoot, so that this book can help the distance lecture process become more interesting. and effective both in presenting the material, the media used to evaluate learning in lectures. The results of this study show that the Digital Book was developed to conclude that it is feasible, interesting and effective to be used as a distance learning medium and helps students in increasing self-efficacy in learning.